Menganalisis Faktor Yang Mempengaruhi Konsumen Dalam Pembelian Sepeda Motor - Arnoldus Ngongo; Jefrianus Adi Ama; Agustinus Samba Lalo; Norbertus Bili; Angela Marici Wendelin Lete Boro; Anggriani Eti Bulu,; Emerliati Dappa Bussa (Venus: Jurnal Publikasi Rumpun Ilmu Teknik, 2024)
Changes in society and technological developments that occur in the current era of globalization have resulted in the emergence of new products from various companies. This has an impact on companies competing with each other to get consumers who are the targets of each company to market their products. It is not easy for companies to get consumers because they often face problems, especially related to efforts to market their products to the market. Seeing what is described above, marketing is one of the activities carried out by a company to maintain its survival, develop and gain profits and can strengthen its position in facing competing companies. This research aims to find out whether the factors price, image, model, quality, service and spare parts can significantly influence consumers to be loyal to Honda brand motorbikes partially or together, and between these factors. What factors have the most significant influence on consumers. This research was carried out by providing a simple service by giving questionnaires to 100 respondents who were considered to represent this research